REPORT ON THE INTERNATIONAL CONFERENCE «UROGENITAL INFECTION AND TUBERCULOSIS» - I. G. Felker; E. V. Kulchavenya (Вестник урологии)
The article presents a report on the international conference «Urogenital infections and tuberculosis», held in Novosibirsk from 24 to 26 October 2013.